PENDUGAAN POTENSI ROTAN DI KAWASAN HUTAN PRODUKSI TERBATAS (HPT) KELOMPOK HUTAN SUNGAI TENUNGUN KECAMATAN BUNUT HULU KABUPATEN KAPUAS HULU KALIMANTAN BARAT - Sujoko, Siswo; Manulang, Efendi; Lidiawati, Ina (Universitas Tanjungpura, 2013)
Preservation of natural resources such as rattan currently experiencing problems due to the difficulty and away in the forest by collecting rattan entered. This is due to natural forests in tumbuhi rattan pressed by the presence of, among others, land clearing, shifting cultivation and for other purposes so that the potential of rattan is reduced. The research was conducted in Limited Production Forest (HPT) forest group Tenungun Rivers Nanga Two District Bunut Hulu Kapuas Hulu in West Kalimantan. The method used for sampling is a method with a sample unit is not disconnected transects (Continuous strip sampling) research plot area is 16 acres, a square with a size of 400 mx 400 m. Furthermore, in the plot lines of the observation made ??by 40 lines Based on the results of the study found as many as 10 species of rattan. As for the types of rattan found in the study plots that petit rattan (Calamus spectobilis), Ilam rattan (Karthalsia momboides), Jerenang rattan (Daemonorops drancellus), shrimp rattan (Karthalsia schenomerathus), Jelapang rattan (Calamus momboides), Single rattan (Calamus mucromathus), Sega rattan (Calamus caesius), Lowa rattan (Plectocomiopsis geminiflorus Becc), wicker rattan (Korthalsia flagellaris Miq), and Marau rattan (Calamus mattenensis Becc). Potential 193.06 rattan stems per hectare, with a wet weight of 1355.89 kg per hectare. Key words : Rattan, Limited Production Forest, Tenungun Rive